Analisis Manajemen Waktu Siswa Sekolah Dasar Melalui Jurnal Harian - Maulida Fazidatur Rofi; Tsania Sakinatun Nisa; Aditya Hening Widyastuti; Muhammad Nofan Zulfahmi (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
The use of daily journals as a time management tool among elementary school students has significant benefits in helping them identify priorities, set goals, and manage the balance between studying and playing. By recording daily activities, students can monitor the allocation of time spent on productive and non-productive tasks, allowing them to develop good habits from an early age. Research shows that daily journals not only improve learning efficiency but also help students become more organized, reduce stress levels, and enhance time management skills that will be useful in the future. For successful implementation, structured strategies are needed, including training for students, the design of engaging journals, and active involvement from teachers and parents in monitoring and providing guidance. While challenges such as students' inconsistency in filling out journals and time limitations exist, solutions like reward systems and simplifying activity logging can be applied. Regular evaluations, through weekly reflections and feedback from teachers, allow students to improve their time management and boost academic performance. Collaboration between teachers and parents plays a crucial role in enhancing the effectiveness of daily journals as a learning tool that supports better time management for students.